2015
DOI: 10.1103/physrevd.92.115012
|View full text |Cite
|
Sign up to set email alerts
|

Quark-flavored scalar dark matter

Abstract: It is an intriguing possibility that dark matter (DM) could have flavor quantum numbers like the quarks. We propose and investigate a class of UV-complete models of this kind, in which the dark matter is in a scalar triplet of an SU(3) flavor symmetry, and interacts with quarks via a colored flavor-singlet fermionic mediator. Such mediators could be discovered at the LHC if their masses are ∼ 1 TeV. We constrain the DM-mediator couplings using relic abundance, direct detection, and flavor-changing neutral-curr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 100 publications
1
30
0
Order By: Relevance
“…22 It is also evident that the DM can be stable only if it is lighter than the t-channel mediator. In order to avoid possible occurrence of flavour violating effects, with consequent strong constraints on the couplings λ Ψ u,d,Q (λ u,d,Q ), we assume that the mediator carries also a flavour quantum number (a "flavored DM" [278][279][280] would be equally feasible), for…”
Section: T-channel Portalsmentioning
confidence: 99%
“…22 It is also evident that the DM can be stable only if it is lighter than the t-channel mediator. In order to avoid possible occurrence of flavour violating effects, with consequent strong constraints on the couplings λ Ψ u,d,Q (λ u,d,Q ), we assume that the mediator carries also a flavour quantum number (a "flavored DM" [278][279][280] would be equally feasible), for…”
Section: T-channel Portalsmentioning
confidence: 99%
“…The nucleon tensor charge is the linear coefficient which relates the quark EDM to the nucleon EDM, and the extraction from experimental data shows values smaller than one [131][132][133][134]. Recent lattice QCD analyses give also consistent data [135][136][137][138][139][140][141][142][143]. It is suggested that nucleon charges which give the quark spin in the nonrelativistic limit, such as the axial or tensor charges, are suppressed by the dynamical gluon dressing [144][145][146].…”
Section: Prospects To the Discovery Of New Physicsmentioning
confidence: 99%
“…We are extending the calculation of the chromo-EDM by constructing various combinations of the matrix elements that each provide an estimate of F 3 , and by adding the contribution of the disconnected diagrams. To address divergent mixing under renormalization, the RI-sMOM scheme defined in [10] is complicated, so we are evaluating gradient-flow regularization [23]. We will first implement this scheme for the simpler case of the two gluonic operators.…”
Section: Ongoing Workmentioning
confidence: 99%